2014
DOI: 10.1165/rcmb.2013-0114oc
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lung Epithelium in Neutrophil Recruitment during Pneumococcal Pneumonia

Abstract: Epithelial cells line the respiratory tract and interface with the external world. Epithelial cells contribute to pulmonary inflammation, but specific epithelial roles have proven difficult to define. To discover unique epithelial activities that influence immunity during infection, we generated mice with nuclear factor-κB RelA mutated throughout all epithelial cells of the lung and coupled this approach with epithelial cell isolation from infected and uninfected lungs for cell-specific analyses of gene induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 44 publications
5
88
1
Order By: Relevance
“…LPS-induced acute lung injury is marked by increased neutrophil influx and up-regulation of proinflammatory cytokines. Similar phenotypes are observed in other lung inflammatory conditions, including asthma (6), chronic obstructive pulmonary disease (7), and pneumonia (8,9). LPS-mediated lung inflammation is associated with breast and colon cancer metastasis to the lungs (10)(11)(12).…”
supporting
confidence: 52%
“…LPS-induced acute lung injury is marked by increased neutrophil influx and up-regulation of proinflammatory cytokines. Similar phenotypes are observed in other lung inflammatory conditions, including asthma (6), chronic obstructive pulmonary disease (7), and pneumonia (8,9). LPS-mediated lung inflammation is associated with breast and colon cancer metastasis to the lungs (10)(11)(12).…”
supporting
confidence: 52%
“…Neutropenic human patients (39,40) and laboratory mice (36,41,42) have enhanced susceptibility to pseudomonal pneumonia. Inefficient rapid, early neutrophil recruitment, even when corrected within 24 hours, resulted in 10-fold more bacteria in the airspaces at 48 hours in a murine model of pneumococcal pneumonia (43). Potentiating the early phase of neutrophil recruitment may represent a therapeutic approach in the age of antibiotic resistance.…”
Section: High-affinity B 2 Integrins and Neutrophil Effector Functionmentioning
confidence: 99%
“…Specific cell sources of Miwi2 expression were interrogated in mice infected with S. pneumoniae using a previously described protocol for isolating purified cell populations recovered from whole lung enzymatic digests and bronchoalveolar lavage fluid (3,16 ized in the cytoplasm, and restricted to airway cells ( Figure 1E). To determine whether the increase in Miwi2 mRNA correlated with increased MIWI2 protein expression, tissue sections isolated from uninfected or infected lungs were quantitatively compared, and demonstrated that the number of MIWI2-positive cells was significantly increased as a result of infection ( Figure 1F).…”
Section: Miwi2 Is Expressed In Adult Lungs and Induced During Pneumocmentioning
confidence: 99%
“…-cells from whole lung digests contain the major pulmonary epithelial subtypes, including club cells, multiciliated cells, and type I and II pneumocytes (16). We evaluated lung sections by immunohistochemistry to determine the cell type and anatomic location of MIWI2 protein expression in the lungs.…”
Section: Cd45mentioning
confidence: 99%
See 1 more Smart Citation